Avaliação da toxicidade reprodutiva da sinvastatina em Ratos machos adultos - Banzato, Thais Petrochelli [UNESP] (2013)
Statins are lipid lowering agents extensively used in human clinical medical. They exert their effects through inhibition of HMG-CoA reductase, a crucial enzyme in cholesterol synthesis. Since cholesterol is the precursor of steroid hormones, drugs that decrease cholesterol may damage male reproductive function. Investigate the effects of the exposure to different doses of simvastatin on the reproductive parameters of adult male Wistar rats. Thirty rats were randomly assigned into three groups: simvastatin (20 or 40 mg/kg), control (vehicle - DMSO/oil), and were treated for 30 days orally for evaluation of reproductive parameters after euthanasia. Weight of the reproductive organs; sperm counts, motility and morphology; histopathology; hormonal levels and fertility. The weight of reproductive organs, sperm motility and histopathology analysis were similar among groups. There was a decrease in sperm production and epididymis sperm number, uterus weight with fetuses, implant and live fetuses numbers in simvastatin groups. The animals exposed to simvastatin showed an increase in the pre-implantation loss and sperm with abnormal morphology. The observed effects on reproductive parameters could be associated with toxic effects of simvastatin on spermatogenesis, causing potential damage to male fertility